Carotid intima-media thickness as a marker for assessing the severity of coronary artery disease on coronary angiography - Wani, Asif S.; ., Zafirah; Rashid, Samia; Tantray, Hanief M. (International Journal of Research in Medical Sciences, 2018)
Background: Coronary artery disease (CAD), the leading cause of death worldwide, has a huge area of primary prevention where patients at risk can be identified for more intensive, evidence-based medical interventions to reduce cardiovascular events. Whereas coronary angiography has stood the test of time to assess atherosclerotic burden, it is still unavailable to a huge population at risk of CAD. This study was devised in search of a cheap and simple tool to assess atherosclerotic burden. We aimed to investigate the relationship between Carotid Intima Media Thickness (CIMT) and Coronary Artery Disease (CAD) in patients evaluated by coronary angiography for suspected CAD and whether CIMT could predict the extension of CAD. Methods: This study was a cross-sectional study conducted from March 2013 to September 2015 in Department of Medicine, SMHS Hospital, J and K, India. A total of 100 patients admitted to for undergoing coronary angiography indicated for suspected coronary artery disease were enrolled. the risk factors evaluated in this study included age, body mass index, sex, dyslipidemia, hypertension, diabetes mellitus and smoking. CAD was assessed and classified by coronary angiography and CIMT was assessed by carotid doppler. Results: There was a positive relationship between CIMT and CAD. Risk factors like Age, smoking, BMI, cholesterol, hypertension, and diabetes had significant positive effect on CIMT; whereas gender, VLDL, triglycerides, HDL and LDL were statistically insignificant in affecting CIMT. Conclusions: CIMT is a cheap and simple tool to predict the extent of CAD.